The Impact of Macroeconomic Factors On Issuing Sukuk - A. Soliman, Hebatallah; El-Elhalaby, Sherif; Aboul-Dahab, Sameh (The Arab Journal of Administration, 2022)
This study seeks to measure the effect of macroeconomic factors which are Inflation; GDP; Exchange Rate; Openness, and Domestic Credit in addition to the impact of corporate governance of country based on Worldwide Governance Indicators (WGI) on the value of issued Sukuk. The study also seeks to measure the impact of culture based on Hofsted model on the value of issued Sukuk. This study uses data for 277 different institutions and governments across 8 countries which are UAE; KSA; Qatar; Malaysia; Oman; Bahrain; Turkey and Kuwait for period between 2011 and 2017. As far as we know, this is one of the original and updated studies that investigate these relationships. Consistent with our predictions related to the impact of macro factors on issuing Sukuk.the empirical results indicate a positive association with Domestic Credit; Inflation and GDP and find no association with exchange rate. Concerning with the impact of Governance Indicators; we find a positive impact for rule of law and insignificant for other variables. Our analysis also shows a positive impact for culture based on long term orientation and uncertainty avoidance on the value of issued Sukuk. This study adds value for how macroeconomic factors work as a motivator or constrained for issuing Sukuk in different markets